An energy efficient NOMA-based spectrum sharing techniques for cell-free massive MIMO. (5th September 2022) - Gangadhar, Ch.; Chanthirasekaran, K.; Chandra, K. Ramesh; Sharma, Aditi; Thangamani, M.; Kumar, Ponnusamy Siva
In this paper, a hybrid spectrum optimisation strategy is introduced to enhance resource sharing capability concerning variable sum rate and minimum interference ratio of the secondary users (SUs) for cell-free massive multiple input multiple output (CF-MIMO) system and induce energy using non-orthogonal multiple access (NOMA) resource allocation-based algorithm. The proposed optimistic clustering method includes the secondary users (SUs) placed in different radical coverage with fixed distance forming irregular cluster group size depend upon their interference degree and converges dynamic stability. The NOMA-RA algorithm enhances the variable sum rate by assigning different cluster groups, conquering with suitable sub-channels. The simulation parameters are normalised interference ratio, pilot insertion, received signal strength (RSS), successive interference cancellation (SIC) and uplink and downlink transmission power. As the results show, significant improvement is achieved by the available amount of SUs in terms of variable sum rate and minimum interference ratio as compared with CF-MIMO and NOMA, respectively.